Microstructured optical fiber Bragg grating as an internal three-dimensional strain sensor for composite laminates. (31st March 2015) - Sonnenfeld, Camille; Luyckx, Geert; Sulejmani, Sanne; Geernaert, Thomas; Eve, Sophie; Gomina, Moussa; Chah, Karima; Mergo, Pawel; Urbanczyk, Waclaw; Thienpont, Hugo; Degrieck, Joris; Berghmans, Francis
Abstract: In this article, we study the possibility to use a pair of specifically designed microstructured optical fiber Bragg gratings (MOFBGs) as a multi-component strain sensor when embedded within composite materials. The dependence on the orientation of the transverse sensitivity of the MOFBGs is exploited to build a sensing device able to measure the strain field along the three principal mechanical directions of a laminate composite. We developed an analytical and numerical model of such a sensor and benchmarked it with experiments performed on laminated composite coupons equipped with this sensor. We report on a theoretical strain resolution of about 5 μϵ in the transverse directions of the composite material, which is a six-fold improvement over results reported in literature.